2003
DOI: 10.1002/anie.200352201
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Quantitative Solid‐State Synthesis of Carbon Nanotubes from Homogeneous Diphenylethynecobalt and –Nickel Complexes

Abstract: Carbon nanotubes (CNTs) have generated a tremendous amount of research interest because of their unique structural, electronic, magnetic, and mechanical properties. [1] Among the various synthetic methods employed for their preparation, chemical vapor deposition (CVD) has emerged to be most effective, and efforts are increasing in applying this technique to pre-growth device fabrication by utilizing (in particular lithographically) [2] patterned catalyst arrays and in situ tube assembly. [2,3] Crucial in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 69 publications
0
47
1
2
Order By: Relevance
“…The solid-state pyrolysis of organometallic compounds such as metallo-dehydro[n]annulenes has emerged as a new method for making CNTs (primarily MWNTs). [376][377][378][379] The pyrolysis of an HBC-cobalt complex 141 in the solidstate produces carbon nanotubes ( Figure 13). [380] Nearly quantitative yields of either "bamboo-shaped" or straight nanotubes are obtained.…”
Section: From Discotic Mesophases To Carbon Nano-and Microstructuresmentioning
confidence: 99%
“…The solid-state pyrolysis of organometallic compounds such as metallo-dehydro[n]annulenes has emerged as a new method for making CNTs (primarily MWNTs). [376][377][378][379] The pyrolysis of an HBC-cobalt complex 141 in the solidstate produces carbon nanotubes ( Figure 13). [380] Nearly quantitative yields of either "bamboo-shaped" or straight nanotubes are obtained.…”
Section: From Discotic Mesophases To Carbon Nano-and Microstructuresmentioning
confidence: 99%
“…Various methods have been developed for the synthesis of CNTs, such as arc discharge [3], laser vaporization of a graphite electrode in the presence of metal catalysts [4], catalytic decomposition of hydrocarbon vapor over a transition metal incorporated silica or zeolite support [5,6], pyrolysis of metallocene [7], detonation-assisted synthesis [8], etc. Recently, it was reported that CNTs can also be synthesized by solid-phase transformation of carbonaceous materials containing metal particles [9][10][11]. Various kinds of materials, such as carbon black, amorphous carbon, fullerene soot and kinds of polymers can be used as raw materials in the solid-phase transformation synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Die Autoren vermuteten daher, dass der Prozess mit einer Cyclotrimerisierung des Übergangsmetallkomplexes beginnt. [189] Die Komplexierung von PAKs mit Cobalt-Katalysatoren wurde mit Hexakis(1-dodecylethinyl)-HBC und [Co 2 (CO) 8 ] realisiert, wobei die eigentliche Komplexierung über die Acetylenreste des HBC-Derivats erfolgte. Nach erstem Erhitzen auf 250 8C fand die Pyrolyse bei 600 8C, 800 8C oder 1000 8C statt.…”
Section: Selbstorganisation Von Polycyclischen Aromatischen Kohlenwasunclassified
“…Mitunter enthielten die Spitzen kleine Cobaltkristalle. [189] ¾hnlich zu der Herstellung von Kohlefasern aus Polyacrylnitril lassen sich Polymere als Vorstufen unter Erhaltung ihrer mesoskopischen Struktur zur Herstellung nanostrukturierter Kohlenstoffmaterialien in der Übergangsmetall-katalysierten Pyrolyse einsetzen. Zum Beispiel synthetisierten Jang und Yoon Nanopartikel bestehend aus Polypyrrol (PPy) mit einem Durchmesser von 62 nm durch Emulsionspolymerisation von Pyrrol mit FeCl 3 .…”
Section: Pyrolyse Heteroaromatischer Verbindungenunclassified